BIOLOGICAL AND ELECTRICAL RESISTANCE OF ACETYLATED FLAX FIBRE REINFORCED POLYPROPYLENE COMPOSITES - Andrzej Korneliusz Bledzki; Marta Lucka; Abdullah Al Mamun; Janusz Michalski (BioResources, 2009)
Flax fibre reinforced polypropylene composites were fabricated using a high speed mixer followed by injection moulding. Prior to composite production, the fibre was modified by acetylation in the presence of perchloric acid. The effect of acetylation of the fibre was assessed on the basis of moisture resistance and dielectric properties of the resulting composites. It was found that the moisture absorption and swelling properties of the composites were reduced respectively by 60% and 30% due to acetylation. Two different types of biocide were mixed with untreated flax fibre, and the samples were exposed to decay fungi for up to 3 months along with control polypropylene. The composites with acetylated fibres showed good protection against fungi, and biocide had less effect on biological resistance. The dielectric properties of the flax-polypropylene composites were also estimated as a function of aging period. The composites with modified fibre showed more improvement in dielectric properties compared to the composites with untreated fibres. The mechanical properties were investigated for those composites. Tensile and flexural strengths of composites were found to be increased following acetylation due to modification, and strength properties of both untreated and acetylated flax fibre reinforced polypropylene composites decreased with respect to aging period. The Charpy impact strengths of composites were found to increase with increasing aging periods.